Superovulation and embryo quality with porcine follicle stimulation hormone (pFSH) in Katahdin hair sheep during breeding season - Sánchez Dávila, Fernando; Bernal Barragán, Hugo; Del Bosque González, Alejandro S.; González Gómez, Adán; Olivares Sáenz, Emilio; Padilla Rivas, Gerardo Raymundo; Ledezma Torres, Rogelio Alejandro (Academic Journals, 2013)
Estrus synchronization of 21 ewes was carried out using intravaginal sponges (60 mg of medroxyprogesterone acetate, Sincrogest®-Sanfer, Mexico) for 14 days. 7 ewes were randomly assigned to one of the three treatments: T1, 80 mg; T2, 120 mg; T3, 140 mg of porcine follicle stimulating (pFSH) (Folltropin-p®-Bioniche, Canada) administered on day 12 after sponge insertion. The dose was divided in decreasing doses; second and third day representing 50 to 75% and 25 to 33% of the first day dose, respectively. At the beginning of superovulation treatment, each ewe received 5 mg of dinoprost tromethamine (1 ml of Lutalyse® Pfizer, Mexico). An effect of pFSH level was observed on the interval from sponge removal and the onset of estrus (REI) (P < 0.01), with a difference of 13.5 h between ewes from treatment 2 and 3. The number of follicles (F), number of collected embryos (CE) and transferable embryos (TE) (P < 0.05) was also different among treatments, with highest values observed in T3 (3.0 ± 0.6 for CE and 2.3 ± 0.5 for TE). Embryo recovery rate was in average 66.5%, (P > 0.05) of CL observed. Further investigation is guaranteed to evaluate the effect of pFSH doses on estrus synchronization for selected breeding seasons